Profile of parent participation in supporting learning activities at elementary school - Maulinah, Maulinah (Jurnal Inovasi Guru Indonesia, 2024)
Background: Parental participation constitutes a critical component of primary education, contributing significantly to children’s academic achievement, motivation, and socio-emotional development. Although previous studies have established a positive association between parental involvement and student performance, variations in the forms and intensity of participation remain influenced by demographic and contextual factors. Objective: This study aimed to describe the profile of parental participation in supporting learning activities at the elementary school level and to identify demographic factors associated with variations in involvement. Methods: A descriptive quantitative design was employed. Data were collected from 150 parents of students in Grades 4–6 using structured questionnaires with Likert-scale items measuring home-based involvement, school-based participation, emotional support, and academic assistance. Demographic variables included parents’ educational level and employment status. Descriptive statistics (frequencies and percentages) were used to summarize participation patterns, while chi-square analysis was conducted to examine associations between demographic characteristics and levels of involvement. Results: The findings indicated that the majority of parents demonstrated moderate to high levels of participation. Approximately 60% frequently supported their children’s learning at home, and 55% attended school meetings or activities. Emotional support was reported by 70% of respondents, while 65% provided academic assistance. Parental participation was significantly associated with educational background and work flexibility, with higher involvement observed among parents with higher educational attainment and flexible working schedules. Time constraints due to employment emerged as the primary barrier to school-based participation. Conclusion: Parental participation in elementary education is generally positive but varies according to demographic factors, particularly educational level and occupational demands. Strengthening school–parent communication and providing flexible engagement opportunities are essential to enhancing sustained parental involvement in supporting children’s learning.